Motivational Projections of Russian Spontaneous Speech - Shipitsina, Galina M.; Kharchenko, Vera K.; Ogneva, Elena A.; Levina, Ella M.; Yakimova, Ekaterina M. (Journal of History Culture and Art Research, 2017)
The article deals with the semantic, pragmatic and structural features of words, phrases, dialogues motivation, in the contemporary Russian popular speech. These structural features are characterized by originality and unconventional use. Language material is the result of authors` direct observation of spontaneous verbal communication between people of different social and age groups. The words and remarks were analyzed in compliance with the communication system of national Russian language and cultural background of popular speech. Studies have discovered that in spoken discourse there are some other ways to increase the expression statement. It is important to note that spontaneous speech identifies lacunae in the nominative language and its vocabulary system. It is proved, prefixation is also effective and regular way of the same action presenting. The most typical forms, ways and means to update language resources as a result of the linguistic creativity of native speakers were identified.